Pjera Robina sindroma heterogenitātes pārskats - Rezaeitazangi, Rayyan (Latvijas Universitāte, 2023)
Pjēra Robina secība (PRS) ir reta ģenētiska saslimšana, kas skar galvaskausa un sejas struktūru attīstību, tostarp žokli un mēli. Precīza PRS izplatība nav labi zināma, taču tiek lēsts, ka tā skar 1 no 8500 līdz 1 no 22 000 dzīvi dzimušajiem. Lai arī PRS ir komplicēts galvaskausa un sejas struktūru attīstības traucējums, ko izraisa ģenētisku mutāciju un vides faktoru kombinācija, tā precīze etioloģija vēl nav pilnībās skaidra. Pētījumi ir parādījuši, ka PRS var izraisīt mutācijas tādos gēnos gēnos kā SOX9, TBX1 un DGCR2. PRS var būt saistīta arī ar citiem sindromiem, piemēram, Stiklera velocardiofaciālo, Tričera-Kolinsa, CHARGE uc. Šis padziļinātais literatūras pārskats tika veikts, lai izpētītu PRS dažādos aspektus.

Pierre Robin Sequence (PRS) is a rare genetic disorder that affects the development of craniofacial structures, including the jaw and tongue. The exact prevalence of PRS is not well known, but it is estimated to affect 1 in 8,500 to 1 in 22,000 live births. The aetiology of PRS has yet to be fully understood. In order to understand the sequence and its background, a profound literature review was performed to learn more about the syndrome and its different aspects. PRS is considered a complex disorder that results from a combination of genetic mutations and environmental factors that affect the development of craniofacial structures. Studies have shown that mutations in genes such as SOX9, TBX1, and DGCR2 can lead to the development of PRS. Pierre Robin Sequence can also be associated with other syndromes such as Stickler, Velocardiofacial, Treacher-Collins, and CHARGE.
Overview of heterogeneity of Pierre Robin sequence
Keywords: Medicīna; Pierre Robin Sequence; Micrognathia; Glossoptosis; Cleft palate; Stickler syndrome